A2_8 Sunshades for the Earth - Wilson, Mark; Evill, Ry; Johnson, Christopher; Rolfe, Samantha (Physics Special Topics, 2009)
This article examines the theoretical size of a sunshade that could be employed to combat the heating effects of climate change. It is found that a change in emissivity of as little as 0.06 could result in a global mean temperature change of around 4 K. To counteract this temperature change, a sunshade of area 7.45x1012 m2 placed at the L1 point would be required.